Effect of herbal decoctions used in Mexican traditional medicine attenuate the adverse effects of a hypercaloric diet. - Ana K. Castellanos-Jiménez; Rosalía Reynoso-Camacho; Nuria E. Rocha-Guzmán; María A. Corella-Madueño; Erika A. de los Ríos; Luis M. Salgado (Elsevier, 2022)
Background: In Mexico, plants as Ibervillea sonorae, Justicia spicigera, Mentha spicata, or Hibiscus sabdariffa are used to prepare decoctions that are traditionally used by the population to prevent or treat several diseases such as obesity and diabetes; scientific evidence is still in process. Purpose: This study evaluated the therapeutic effects of traditional preparations (aqueous decoctions) of four herbs on obesity and its complications, such as insulin resistance, hypertriglyceridemia, and hepatic steatosis induced by a hypercaloric diet. Materials and methods: UPLC-PDA-ESI-QqQ analysis was performed to identify and quantify extractable phenolic constituents of each decoction. Metabolic alterations were induced by high fat and fructose diet in Wistar rats; decoctions were administered for 12 weeks. The effects of herbs on insulin resistant animals, glucose tolerance, insulin resistance, hypertriglyceridemia, and lipid storage in the liver and adipose tissue were assessed by biochemical assays and histological examination. Results: Rats treated with H. sabdariffa preventing body weight gain, improving glucose homeostasis, and decreasing adipocyte size. Meanwhile, the triglycerides and glucose levels in obese rats decreased after I. sonorae treatment. All decoctions showed no adverse effects. UPLC-PDA-ESI-QqQ analysis revealed caffeoylquinic acid derivatives as the most abundant phenolic compounds in aqueous decoctions. Conclusions: Decoctions of H. sabdariffa or I. sonorae attenuated the adverse effects of a hypercaloric diet via improving glucose homeostasis and triglycerides levels without any observed adverse effects. These decoctions could be helpful for the treatment of metabolic diseases such as obesity and its complications.